Neonatal Screening for Primary Carnitine Deficiency: Lessons Learned from the Faroe Islands - Ulrike Steuerwald; Allan M. Lund; Jan Rasmussen; Nils Janzen; David M. Hougaard; Nicola Longo (MDPI AG, 2017)
Primary carnitine deficiency is caused by the defective OCTN2 carnitine transporter encoded by the SLC22A5 gene. A lack of carnitine impairs fatty acid oxidation resulting in hypoketotic hypoglycemia, hepatic encephalopathy, skeletal and cardiac myopathy, and arrhythmia. This condition can be detected by finding low levels of free carnitine (C0) in neonatal screening. Mothers with primary carnitine deficiency can also be identified by low carnitine levels in their infant by newborn screening. Primary carnitine deficiency is rare (1:40,000-1:140,000 newborns) except in the Faroe Islands (1:300) due to a founder effect. A specific mutation (c.95A>G, p.N32S) is prevalent, but not unique, with three additional mutations (c.131C>T/p.A44V, a splice mutation c.825-52G>A, and a risk-haplotype) recently identified in the Faroese population. In the Faroe Islands, several adult patients suffered sudden death from primary carnitine deficiency leading to the implementation of a nationwide population screening (performed after 2 months of age) in addition to universal neonatal screening. While most affected infants can be identified at birth, some patients with primary carnitine deficiency might be missed by the current neonatal screening and could be better identified with a repeated test performed after 2 months of age.